Functional plasticity of a peroxidase allows evolution of diverse disulfide-reducing pathways - Faulkner, Melinda J; Veeravalli, Karthik; Gon, Stéphanie; Georgiou, George; Beckwith, Jon (Proceedings of the National Academy of Sciences - PNAS, 2008)
In Escherichia coli, the glutathione/glutaredoxin and thioredoxin pathways are essential for the reduction of cytoplasmic protein disulfide bonds, including those formed in the essential enzyme ribonucleotide reductase during its action on substrates. Double mutants lacking thioredoxin reductase (trxB) and glutathione reductase (gor) or glutathione biosynthesis (gshA) cannot grow. Growth of Deltagor DeltatrxB strains is restored by a mutant (ahpC*) of the peroxiredoxin AhpC, converting it to a disulfide reductase that generates reduced glutathione. Here, we show that ahpC* also restores growth to a DeltagshB DeltatrxB strain, which lacks glutathione and accumulates only its precursor gamma-glutamylcysteine (gamma-GC). It suppresses this strain by allowing accumulation of reduced gamma-GC, which can substitute for glutathione. Surprisingly, new ahpC suppressor mutations arose in a DeltagshA DeltatrxB strain lacking both glutathione and gamma-GC, a strain that ahpC* does not suppress. Some of these mutant AhpC proteins channel electrons into the disulfide-reducing pathways via either the thioredoxins or the glutaredoxins without, evidently, the intermediary of glutathione. Our results provide insights into the physiological functioning of the glutathione pathway and reveal surprising plasticity of a peroxidase because different mutant versions of AhpC can channel electrons into the disulfide-reducing pathways by at least four distinct routes. Despite the reductase activity of mutant AhpCs, these various suppressor strains exhibit an oxidizing cytoplasm and accumulate correctly folded disulfide-bonded proteins in their cytoplasm. Proteins most effectively oxidized vary between strains, potentially providing useful tools for expressing different disulfide-bonded proteins.